Expanding the phenotype of X‐linked SSR4–CDG: Connective tissue implications. Issue 2 (21st December 2020) - Castiglioni, Claudia; Feillet, François; Barnerias, Christine; Wiedemann, Arnaud; Muchart, Jordi; Cortes, Fanny; Hernando‐Davalillo, Cristina; Montero, Raquel; Dupré, Thierry; Bruneel, Arnaud; Seta, Nathalie; Vuillaumier‐Barrot, Sandrine; et al.
Abstract: Signal sequence receptor protein 4 (SSR4) is a subunit of the translocon‐associated protein complex, which participates in the translocation of proteins across the endoplasmic reticulum membrane, enhancing the efficiency of N‐linked glycosylation. Pathogenic variants in SSR4 cause a congenital disorder of glycosylation: SSR4–congenital disorders of glycosylation (CDG). We describe three SSR4–CDG boys and review the previously reported. All subjects presented with hypotonia, failure to thrive, developmental delay, and dysmorphic traits and showed a type 1 serum sialotransferrin profile, facilitating the diagnosis. Genetic confirmation of this X‐linked CDG revealed one de novo hemizygous deletion, one maternally inherited deletion, and one de novo nonsense mutation of SSR4 . The present subjects highlight the similarities with a connective tissue disorder (redundant skin, joint laxity, blue sclerae, and vascular tortuosity). The connective tissue problems are relevant, and require preventive rehabilitation measures. As an X‐linked disorder, genetic counseling is essential.